1998
DOI: 10.1037/0022-3514.74.4.837
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous trait transference: Communicators take on the qualities they describe in others.

Abstract: Spontaneous trait transference occurs when communicators are perceived as possessing the very traits they describe in others. Study 1 confirmed that communicators become associated with the trait implications of their descriptions of others and that such associations persist over time. Study 2 demonstrated that these associations influence specific trait impressions of communicators. Study 3 suggested that spontaneous trait transference reflects simple associative processes that occur even when there are no lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
215
5
9

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(248 citation statements)
references
References 27 publications
18
215
5
9
Order By: Relevance
“…It is interesting that this mechanism is inconsistent with trait rating results reported by Skowronski et al (1998) and Mae et al (1999). Their research on spontaneous trait transference suggests that implications of spontaneously inferred traits probably do not include general halo effects.…”
Section: Spontaneous Antonyms: Going Beyond Initial Inferencesmentioning
confidence: 85%
“…It is interesting that this mechanism is inconsistent with trait rating results reported by Skowronski et al (1998) and Mae et al (1999). Their research on spontaneous trait transference suggests that implications of spontaneously inferred traits probably do not include general halo effects.…”
Section: Spontaneous Antonyms: Going Beyond Initial Inferencesmentioning
confidence: 85%
“…The central aim of the current research was to examine the extent to which these stereotype-based inference processes are moderated by the availability of processing capacity. Research into the efficiency of STIs has shown that, in general, the STI process is neither disrupted nor enhanced by concurrent load (Lupfer, Clark, & Hutcherson, 1990;Winter et al, 1985; but also see Skowronski, Carlston, Mae & Crawford, 1998). This suggests that the STI process is quite efficient (although some interference with the STI process has been found at very high-load levels; Uleman, Newman, & Winter, 1992).…”
Section: Stereotypical Inferences 293mentioning
confidence: 92%
“…For example, research has shown that adults tend to dislike the bearer of information they disagree with even when the bearer of the information herself disagrees with that information being shared (Manis, Cornell, & Moore, 1974) and that adults will see an individual as, for example, more angry if that individual has described another person as angry (Skowronski, Carlston, Mae, & Crawford, 1998). In addition, even novel objects elicit rapid evaluation (Duckworth, Bargh, Garcia, & Chaiken, 2002), and therefore it is not unreasonable to think that quick evaluations occur when observing other humans, a prediction at the heart of the affective tagging hypothesis (Olson, et al, in preparation).…”
Section: Discussionmentioning
confidence: 99%